FKP to assist cluster school to compete at an F1 International Competition for schools - Zuryaty, Zol
Sekolah Menengah Kebangsaan (SMK) Sultanah Hajjah Kalsom is a cluster school for Universiti Malaysia Pahang (UMP)’s Faculty of Manufacturing Engineering (FKP) to enter F1 Competition in Schools Technology Challenge World Final 2013 to be held in November in Texas, US.